Temperament and body weight from ages 4 to 15 years - Kerr, Jessica A; Sutin, Angelina R; Terracciano, Antonio (My University, 2017)
Background/Objectives: In adulthood, conscientiousness and neuroticism are correlates of body weight and weight gain. The present research examines whether the childhood antecedents of these traits, persistence and negative reactivity, respectively, are associated with weight gain across childhood. We likewise examine sociability as a predictor of childhood weight gain and whether these three traits are associated with weight concerns and weight-management strategies in adolescence. Subjects/Methods: Participants (N=4153) were drawn from the Longitudinal Study of Australian Children, an ongoing, population-based study of child and family health and well-being. At the baseline assessment, caregivers reported on their child’s temperament. At every assessment from ages 4–5 to 14–15 years, study children were weighed and measured by trained staff; there were up to six biennial assessments of body mass index and waist circumference. At ages 14–15 years, study children (n=2975) also self-reported on their weight concerns and weight-management strategies. Results: Study children rated lower in persistence or higher in negative reactivity in early childhood gained more weight between the ages of 4 and 15 years. Sociability was associated with weight gain among girls but not among boys. Lower persistence and higher negative reactivity at ages 4–5 years were also associated with greater weight concerns, restrained eating and use of unhealthy weight-management strategies at ages 14–15 years. Conclusions: Childhood traits related to conscientiousness and neuroticism are associated with objective weight gain across childhood and with concerns and strategies to manage weight in adolescence. These results are consistent with a lifespan perspective that indicates that trait psychological functioning contributes to health-related markers from childhood through old age.
Keywords: Child Development; Health -- Body size, BMI, Body image; Health and wellbeing; Childhood and child development; Child Development; Health; Body size, BMI, Body image; Health and wellbeing; Childhood and child development